Sleep Measurement and Health Management Using Fitness Trackers for Elderly People Living Alone - Takagi, Miyako; Tsuchiya, Yosuke; Nakaya, Yusuke; Inoue, Kenrou; Kato, Kei; Fujita, Yukihiro (Advances in Social Sciences Research Journal, 2025)
This study examined the effects of wearable fitness trackers (Fitbit) on sleep monitoring and health awareness among elderly residents of Naraha Town, Fukushima Prefecture—an area affected by the 2011 Great East Japan Earthquake and subsequent nuclear disaster. Elderly individuals, both those living alone and those living with others, wore Fitbits for approximately two weeks, during which their daily sleep duration was recorded and analyzed. In addition, interviews were conducted to assess participants’ experiences and perceived changes in health awareness. Results showed that all participants averaged around six hours of sleep per night, with no statistically significant difference in sleep duration between those living alone and those living with others. However, the visualization of sleep data encouraged self-reflection and health awareness, leading to behavioral changes such as improved sleep hygiene and proactive health consultations. Notably, in a region where prolonged stress and social isolation remain ongoing challenges, daily sleep tracking proved to be a valuable tool for enhancing self-awareness and fostering reassurance among older adults.